2001
DOI: 10.1038/35074506
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of p53 by p14ARF without relocation of MDM2 to the nucleolus

Abstract: The alternative product of the human INK4a/ARF locus, p14ARF, has the potential to act as a tumour suppressor by binding to and inhibiting the p53 antagonist MDM2. Current models propose that ARF function depends on its ability to sequester MDM2 in the nucleolus. Here we describe situations in which stabilization of MDM2 and p53 occur without relocalization of endogenous MDM2 from the nucleoplasm. Conversely, forms of ARF that do not accumulate in the nucleolus retain the capacity to stabilize MDM2 and p53. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
275
3
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(304 citation statements)
references
References 36 publications
22
275
3
4
Order By: Relevance
“…One of the targets is the gene encoding the p19ARF, which is a key component of the p19ARF-MDM2-p53 network (Zhang et al, 1998;Zhu et al, 1999;Trimarchi and Lees, 2002). Activation of p19ARF inhibits MDM2, a p53 ubiquitin ligase, enhancing p53 stabilization (Momand et al, 1992;Kubbutat et al, 1997;Pomerantz et al, 1998;Stott et al, 1998;Zhang et al, 1998;Haupt et al, 1999;Honda and Yasuda, 1999;Weber et al, 1999;Llanos et al, 2001;Zindy et al, 2003). This explains why inhibition of PP-1 activity could lead to observed p53 upregulation in rabbit and rat lens epithelial cells (Li et al, 1998(Li et al, , 2001a.…”
Section: Dephosphorylation Of P53 Displays Strong Impact On Its Functmentioning
confidence: 99%
“…One of the targets is the gene encoding the p19ARF, which is a key component of the p19ARF-MDM2-p53 network (Zhang et al, 1998;Zhu et al, 1999;Trimarchi and Lees, 2002). Activation of p19ARF inhibits MDM2, a p53 ubiquitin ligase, enhancing p53 stabilization (Momand et al, 1992;Kubbutat et al, 1997;Pomerantz et al, 1998;Stott et al, 1998;Zhang et al, 1998;Haupt et al, 1999;Honda and Yasuda, 1999;Weber et al, 1999;Llanos et al, 2001;Zindy et al, 2003). This explains why inhibition of PP-1 activity could lead to observed p53 upregulation in rabbit and rat lens epithelial cells (Li et al, 1998(Li et al, , 2001a.…”
Section: Dephosphorylation Of P53 Displays Strong Impact On Its Functmentioning
confidence: 99%
“…First, while the low levels of Mdm2 that are commonly observed in normal cells preferentially catalyse monoubiquitination of p53 (Li et al, 2003), ARF can not inhibit Mdm2-mediated monoubiquitination of p53 in vivo, although it can block p53 polyubiquitination (Xirodimas et al, 2001). Second, recent studies of p19 ARF demonstrated that ARF is able to cause cell cycle arrest independent of Mdm2 relocalisation to nucleoli and p53 stabilisation (Llanos et al, 2001;Korgaonkar et al, 2002). Thus, a critical question raised is how ARF can efficiently stabilise p53 in normal cells with low levels of Mdm2, a situation where Mdm2 is not solely responsible for p53 degradation.…”
Section: Arf-bp1 a Hect E3 Ubiquitin Ligase Plays An Important Rolementioning
confidence: 99%
“…This has led to conflicting views about how proteins in different sub-nuclear compartments can interact, most of which suggest movement of MDM2 into the nucleolus (Tao and Levine, 1999;Weber et al, 1999Weber et al, , 2000Zhang and Xiong, 1999;Lohrum et al, 2000). We have argued against this idea by showing that versions of human ARF that are excluded from the nucleolus remain capable of binding to MDM2 and stabilizing p53 (Llanos et al, 2001). One such variant, a fusion protein containing the N-terminal 29 residues of human ARF linked to GFP (GFP/2-29), is inherently unstable, but can be stabilized if redirected to the nucleolus by addition of an unrelated basic motif (Llanos et al, 2001;Rodway et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We have argued against this idea by showing that versions of human ARF that are excluded from the nucleolus remain capable of binding to MDM2 and stabilizing p53 (Llanos et al, 2001). One such variant, a fusion protein containing the N-terminal 29 residues of human ARF linked to GFP (GFP/2-29), is inherently unstable, but can be stabilized if redirected to the nucleolus by addition of an unrelated basic motif (Llanos et al, 2001;Rodway et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation